Comparability of self rated health: cross sectional multi-country survey using anchoring vignettes. Issue 7434 (23rd January 2004) - Salomon, Joshua A; Tandon, Ajay; Murray, Christopher J L
Abstract: Objective To examine differences in expectations for health using anchoring vignettes, which describe fixed levels of health on dimensions such as mobility. Design Cross sectional survey of adults living in the community. Setting China, Myanmar, Sri Lanka, Pakistan, Turkey, and United Arab Emirates. Participants 3012 men and women aged 18 years and older (self ratings); subsample of 406 (vignette ratings). Main outcome measures Self rated mobility levels and ratings of hypothetical vignettes using the same questions and response categories. Results Consistent rankings of vignettes are evidence that vignettes are understood in similar ways in different settings, and internal consistency of orderings on two mobility questions indicates good comprehension. Variation in vignette ratings across age groups suggests that expectations for mobility decline with age. Comparison of responses to two different mobility questions supports the assumption that individual ratings of hypothetical vignettes relate to expectations for health in similar ways as self assessments. Conclusions Anchoring vignettes could provide a powerful tool for understanding and adjusting for the influence of different health expectations on self ratings of health. Incorporating anchoring vignettes in surveys can improve the comparability of self reported measures.